2021
DOI: 10.3390/jcm10081692
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Pathological Conditions Affecting Pituitary Stalk

Abstract: Pituitary stalk lesions (PSL) are a very rare pathology. The majority of conditions affecting the infundibulum do not present with clinically apparent symptoms, what makes the diagnosis difficult. The recognition might be also complicated by the non-specific and transient characteristics of hormonal insufficiencies. In our study, we retrospectively analysed demographic, biochemical, and clinical long-term data of 60 consecutive, unselected adult patients (34 women and 26 men) with PSL diagnosed in the Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Depending on the cause of the disorder and the age of the patient, the symptoms of CPHD may have different clinical presentations, indications, and symptoms. In the neonatal period and in early infancy, the most characteristic signs include hypoglycemia, prolonged jaundice, and features of hypogonadism in boys (cryptorchidism, reduced testicle volume, and penile underdevelopment) [ 8 , 9 ]. At preschool or school age, a decrease of growth velocity and short stature dominates.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cause of the disorder and the age of the patient, the symptoms of CPHD may have different clinical presentations, indications, and symptoms. In the neonatal period and in early infancy, the most characteristic signs include hypoglycemia, prolonged jaundice, and features of hypogonadism in boys (cryptorchidism, reduced testicle volume, and penile underdevelopment) [ 8 , 9 ]. At preschool or school age, a decrease of growth velocity and short stature dominates.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical course of patients having pituitary stalk lesions varies from no symptoms to an increase or loss of pituitary function [ 20 ]. Kluczyński et al [ 21 ] reported that among 60 adult patients with pituitary stalk lesions, 5 cases (8.3%) had a clinical presentation of excessive hormone production. However, no PP was observed because the recruited subjects were adults with a mean of 33.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen per cent of patients were diagnosed with concomitant metastases to other central nervous system structures [1]. Stalk involvement was mentioned in 4 reports and one study of 60 consecutive patients with stalk lesions, where, among the whole group, one patient presented NET metastasis to the infundibulum [4]. In a recent literature analysis including 43 patients with PM from NETs, 73% of patients presented with at least one anterior pituitary hormone deficit (gonadal axis insufficiency was the most common).…”
Section: Clinical Vignettementioning
confidence: 99%